2016
DOI: 10.1097/brs.0000000000001606
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Body Mass Index (BMI) and Back or Leg Pain in Patients With Spinal Conditions

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Spine (Phila Pa 1976) The Association between Body Mass Index (BMI) * If the article is to be published pursuant to the "Green" route of Open Access, both the RCUK and the Wellcome Trust require that WKH make the article freely available within six months pursuant to the Attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Given that weight loss has been an important component in the treatment of GTPS to reduce overall tendon microtrauma, it was hypothesized that patients with higher BMI would have higher levels of visceral and subcutaneous body fat correlating to the development of GTPS. However, our results align with recent literature, which indicates that the association of increased BMI to GTPS is equivocal and limited after accounting for confounding factors 18,19 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that weight loss has been an important component in the treatment of GTPS to reduce overall tendon microtrauma, it was hypothesized that patients with higher BMI would have higher levels of visceral and subcutaneous body fat correlating to the development of GTPS. However, our results align with recent literature, which indicates that the association of increased BMI to GTPS is equivocal and limited after accounting for confounding factors 18,19 …”
Section: Discussionsupporting
confidence: 90%
“…However, our results align with recent literature, which indicates that the association of increased BMI to GTPS is equivocal and limited after accounting for confounding factors. 18,19 For our study, we used 3D fat analysis using CT scans, a well-established method in the examination of musculoskeletal diseases. [12][13][14][15][16][17] As such, fat analysis of the CT scans using the 3D autosegmentation tool accurately delineated the boundaries between visceral and subcutaneous fat around the sacropelvic region for our study.…”
Section: Discussionmentioning
confidence: 99%
“…There are no large population studies investigating the relationship between leptin and back pain or disc degeneration. It is clear in the literature that obesity is associated with both low back and leg pain [44]. However, in smaller studies Urquhart et al [18,19] found greater fat mass was associated with increased back pain and reduced disc height and hypothesised biochemical factors as a mediator.…”
Section: Discussionmentioning
confidence: 99%
“…In the group that achieved successful treatment, the probands were on average about 12.5 kg lighter and their BMI was markedly lower than the corresponding values in patients who did not achieve successful treatment. Segar et al [29] showed that a high BMI is associated with pain, especially in the lower extremity; the authors also noted back pain in these patients.…”
Section: Discussionmentioning
confidence: 92%